The great Texas stamp collection : how some stubborn Texas confederate postmasters, a handful of determined Texas stamp collectors, and a few of the world's greatest philatelists created, discovered, and preserved some of the world's most valuable postage stamps - Deaton, Charles (Charles N. Prothro Texana series., 2012)
Among the many difficulties the newly formed Confederate States of America endured in the summer of 1861 was the failure of its post office department to provide sufficient numbers of that item most crucial to its service: the postage stamp. Faced with the resulting din of customer complaints, a handful of industrious Texas postmasters solved the problem by simply making their own homemade stamps.